Primary Hyperparathyroidism: Imaging to Pathology - Piciucchi, Sara (Medknow Publications & Media Pvt Ltd, 2012)
The aim of this review is to describe the multimodal imaging (ultrasound, magnetic resonance, computed tomography, and nuclear medicine) of primary hyperparathyroidism and its correlation to the pathological findings. In the last decades, imaging science has progressed a great deal. Accurate preoperative localization of the involved glands is essential for surgical success.